Wolsey, Wilson and the failure of the Khartoum campaign: an exercise in scapegoating and abrogation of command responsibility - Snook, M. (Cranfield University, 2014)
This thesis is an exercise in military history and takes the form of an investigation into a notable late-nineteenth century blunder; the British Army’s failure to relieve Gordon at Khartoum. It seeks to lay bare operational realities which to date have been obfuscated by substantially successful acts of scapegoating and cover-up. Although political procrastination in Whitehall did not abate until August, the thesis contends that a timely operation of war would still have been possible, if only General Lord Wolseley had recognized that the campaign plan he had designed in April might not, some four months later, be fit for purpose. It proceeds to demonstrate that given revised constraints on time, a full-length Nile Expedition was no longer tenable. Alternative courses of action are also tested. Popular myth would have it that the relief expedition arrived at Khartoum only two days too late. The thesis contends that this is a contrivance propagated by Wolseley out of selfishly motivated concern for his place in history. Wolseley explained away the purportedly critical 48-hours by asserting that Colonel Sir Charles Wilson had unnecessarily stalled the campaign for two days. It was inferred that Wilson was professionally inept, lost his nerve and did not press far enough upriver to be certain that Khartoum had fallen. The thesis traces the course of the ‘Wilson Controversy’, analyses ‘Campaign Design’ and ‘Campaign Management’ in order to identify how and why the relief expedition went awry, and culminates in a closely reasoned adjudication on the validity of the allegations levelled against Wilson. The thesis concludes that the true extent of the British failure was in the order of 60 days; that the failure occurred at the operational level of war, not the tactical; and that accordingly culpability should properly be attributed to Wolseley.
Keywords: Military history; Military leadership